Relacje prawo–intymność „ukryte” w Konstytucji Rzeczypospolitej Polskiej (problem instytucjonalizacji małżeństw homoseksualnych w Polsce wobec nieokreśloności prawa) - Sut, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The aim of this article is to consider the hypothesis: relations between law and intimacy should be described and reflected also on the basis of concepts emerging in social sciences and philosophy. Traditional methods and categories of jurisprudence are not enough here. Relations between the law and intimacy are „hidden”, for example, in art. 47 and art. 18 Polish Constitution. Particularly interesting is art. 18 with the following text: „Marriage as a union of a woman and a man, family, motherhood and parenthood are under the protection and care of the Republic of Poland”. This provision is the cause of a legal dispute over the admissibility of the institutionalization of partnerships in Poland. The problem of the institutionalization of partnerships concerns, in my opinion, the relations between law and intimacy. These relations should be considered on the basis of the results of sociological and philosophical research. To solve the dispute about the admissibility of the institutionalization of partnerships in the Polish Constitution, works of, among others, Michel Foucault and Anthony Giddens may be valuable. M. Foucault’s ideas have a huge impact on the contemporary scientific understanding of sexuality. A. Giddens created the transformation of intimacy concept. The concept is consistent with the axiology of modern legal culture.